Targeted High Resolution LC/MS3 Adductomics Method for the Characterization of Endogenous DNA Damage - Carrà, Andrea; Guidolin, Valeria; Dator, Romel P.; Upadhyaya, Pramod; Kassie, Fekadu; Villalta, Peter W.; Balbo, Silvia (Frontiers in Chemistry, 2019)
DNA can be damaged through covalent modifications of the nucleobases by endogenous processes. These modifications, commonly referred to as DNA adducts, can persist and may lead to mutations, and ultimately to the initiation of cancer. A screening methodology for all known endogenous DNA adducts would be a powerful tool for investigating the etiology of cancer and for the identification of individuals at high-risk to the detrimental effects of DNA damage. This idea led to the development of a DNA adductomic approach using high resolution data-dependent scanning, an extensive MS2 fragmentation inclusion list of all known endogenous adducts, and neutral loss MS3 triggering to profile all DNA modifications. In this method, detection of endogenous DNA adducts is performed by observation of their corresponding MS3 neutral loss triggered events and the relative quantitation using the corresponding full scan extracted ion chromatograms. The method’s inclusion list consists of all known endogenous DNA adducts, compiled and reported here, as well as adducts specific to tobacco exposure to compare the performance of the method with previously developed targeted approaches. The sensitivity of the method was maximized by reduction of extraneous background signal through the purification and minimization of the amount of commercially obtained enzymes used for the DNA hydrolysis. In addition, post-hydrolysis sample purification was performed using off-line HPLC fraction collection to eliminate the highly abundant unmodified bases, and to avoid introduction of plasticizers found in solid-phase extraction cartridges. Also, several instrument parameters were evaluated to optimize the ion signal intensities and fragmentation spectra quality. The method was tested on an animal model of lung carcinogenesis where A/J mice were exposed to the tobacco specific lung carcinogen 4-methylnitrosamino-1-3-pyridyl-1-butanone (NNK) and its effects are enhanced by induction of inflammation from co-exposure of the animals to the pro-inflammatory agent Lipopolysaccharide (LPS). Lung DNA were screened for endogenous DNA adducts known to result from oxidative stress and LPS-induced lipid peroxidation, as well as adducts due to NNK exposure. The detected DNA adducts were then targeted for PRM-MS2 analysis and precise relative quantitation was measured, demonstrating a general workflow for analysis of endogenous DNA adducts.